Callus extract of Ipomoea mauritiana show analgesic and antihyperglycemic activity in Swiss albino mice - Saiful Islam, Md Rasel Ahmed, Rahat Al-Mahamud, Shahnaz Rahman, F.M. Safiul Azam, Rownak Jahan, Mohammed Rahmatullah (Journal of Applied Pharmaceutical Science, 2015)
Callus can be a viable alternative to obtain important phytochemicals and analyze crude extract for pharmacological activities rather than going the cumbersome way of collecting and destroying possibly endangered plants. In this study, callus was produced using nodal explant of Ipomoea mauritiana, and methanol extract of dried and powdered callus was evaluated for its analgesic and antihyperglycemic potential. The extract, when administered to Swiss albino mice at doses of 50, 100, 200 and 400 mg per kg significantly reduced the number of writhings in mice produced by intraperitoneal administration of acetic acid by 23.3, 33.3, 43.3, and 53.3%, respectively. A standard analgesic drug, aspirin, at doses of 200 and 400 mg per kg, reduced the number of writhings by 40.0 and 46.7%, respectively. In oral glucose tolerance tests conducted with glucose-loaded mice, the extract at doses of 50, 100, 200 and 400 mg per kg significantly reduced blood glucose levels by 35.1, 42.5, 53.6, and 58.8%. In comparison, a standard antihyperglycemic drug, glibenclamide, at a dose of 10 mg per kg reduced blood glucose levels by 60.7%. Our study indicates that methanol extract of callus of I. mauritiana can be used to alleviate pain and high blood sugar levels.
Keywords: Analgesic, Ipomoea mauritiana, antihyperglycemic, callus, Convolvulaceae.